Correlation between the ionizing continuum and the variable C iv broad absorption line in multi-epoch observations of SDSS J141007.74+541203.3. Issue 2 (13th June 2019) - Huang, Hong-Yan; Pan, Cai-Juan; Lu, Wei-Jian; Qin, Yi-Ping; Lin, Ying-Ru; Huang, Wei-Rong; Zhou, Yu-Tao; Yao, Min; Nong, Wei-Jing; Lu, Mei-Mei; Yao, Zhi-Kao; Han, Qing-Lin
Abstract: Correlations between the variations of quasar absorption lines and the ionizing continuum have been confirmed recently in systematic studies. However, no convincing individual case is reported. We present a statistical analysis of the variable C iv broad absorption line (BAL) in the quasar SDSS J141007.74+541203.3, which has been observed with 44 epochs by the Sloan Digital Sky Survey Data Release 14. Grier et al. have concluded that the most likely cause of the variability of the BAL in SDSS J141007.74+541203.3 is a rapid response to changes in the incident ionizing continuum. In this paper, we confirm the anticorrelation between the equivalent width of BALs and the flux of the continuum based on the spectra of this quasar, which show significant variations. This serves as further independent evidence for the conclusions of Grier et al.